Measuring Distance, Pointing Address: The Textual Geography of the 'Poem to Coleridge' and 'To W. Wordsworth' - Carlson, Julia (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
This article seeks to revise our understanding of the development of The Prelude by showing how it emerged from a literary exchange that depended on absence. It was not so much a poem prompted by the closeness of Wordsworth and Coleridge as one born of their distance—one that forged a relationship between selves across a temporal and spatial divide by a series of textual devices. These devices, I show, originated in prose and verse sent by mail—in letters that inscribed and sought to overcome distance by using particular forms of address and marks of emphasis: a shared code elaborated on paper rather than in speech. Among these forms of address, the invocation of the “Friend!” (complete with exclamation point) was of particular importance: taken over from the letters, it became a vital part of the poem’s formal, thematic and textual development. It is thus especially unfortunate that the editors of the most popular standard edition of the poem in the twentieth century chose to remove the exclamation point from this and other phrases throughout the 1805 poem, obscuring a crucial aspect of the origination in writing—as a textual address—of what was called the “poem to Coleridge.”